Theoretical research and maintenance of electro hydraulically controlled injectors - A. P. Zhigadlo; Yu. P. Makushev (Вестник СибАДИ)
Introduction. Nowadays the part of the diesel engines for KamAZ-740 cars are operated with fuel equipment, in which the injectors have hydro mechanical control. Their main disadvantage is the low fuel pressure in front of the injector openings (less than 60 MPa) and the lack of fuel supply control.The use of injectors with electro hydraulic control (EHC) increases the pressure in the injector cavity up to 250 MPa and control the fuel injection process. The disadvantage of the injectors with EHC is a structural complexity of a control valve, the difficulty of its regulation and coding. The object of the study is the injectors of KamAZ-740 diesel engine with electro hydraulic control of the atomizer needle stroke.The purpose of this work is to carry out theoretical research and improve the methods of maintenance of injectors with electro hydraulic control (control valve regulation and coding), which will increase their reliability, durability and ensure a reduction in diesel fuel consumption.Research methods. The study of the nozzle control valve is theoretical and calculated. The paper proposes a calculation method and performs theoretical studies for the influence of pressure (50 – 250 MPa) on the value of the effective flow section and the diameter of the nozzle holes of the sprayer.For the injectors with EHC, the control valve regulation procedure has been clarified, which consists in the fact that at the beginning of regulation, the main force acting on the ball from the side of the maximum pressure in the control chamber (for example, 200 MPa) equal to 76 N is calculated (see Figure 4). Then the required spring force of 100 N is determined (20-40% more, see Figure 5). Next, the strength of the electromagnet is estimated at 140 N (20 – 40% more of the spring force, see Figure 6).The results of theoretical research. The results of computational (theoretical) studies for the effective flow section of the sprayer and the diameter of the nozzle holes, depending on the pressure P in front of the nozzle holes, are presented.The paper defines. 1. The forces acting on the ball (57 – 105 N) depending on the pressure in the control chamber (150 – 275 MPa). 2. Spring forces (40 – 140 N) with a stiffness of 40 N /mm, depending on its compression up to 3.5 mm. 3. The forces of the electromagnet (140 – 20 N) depending on the gap between the anchor and the core (0.2 – 0.5 mm).The method of restoring the required (rated) cyclic fuel supply when it changes as a result of replacing the control valve or adjusting is considered. The calculated values of fuel supply per cycle (mm3/cycle) from the activation time are given.Conclusion. The results of the study are intended for organizations and enterprises engaged in diagnostics, restoration, adjustment and coding of injectors with electro hydraulic control for the needle stroke of sprayers. The results of computational studies can be used to refine the methodology of maintenance of fuel systems with electronic control (Common Rail).